Enhanced carbohydrate production by Southern Ocean phytoplankton in response to in situ iron fertilization - van Oijen, T; Veldhuis, MJW; Gorbunov, MY; Nishioka, J; van Leeuwe, MA; de Baara, HJW; de Baar, H.J.W. (Marine Chemistry, 2005)
Storage carbohydrates (e.g., water-extractable beta-1,3-D-glucan in diatoms) are of key importance for phytoplankton growth in a variable light climate, because they facilitate continued growth of the cells in darkness by providing energy and carbon skeletons for protein synthesis. Here, we tested the hypothesis that synthesis of storage carbohydrates by phytoplankton in the Southern Ocean is reduced by low iron and light availability. During the EisenEx/CARbon dioxide Uptake by the Southern Ocean (CARUSO) in situ iron enrichment experiment in the Atlantic sector of the Southern Ocean in November 2000, we studied the dynamics of water-extractable carbohydrates in the particulate fraction over the period of 3 weeks following the iron release. The areal amount (integral between 0- and 100-m depth) of carbohydrates increased from 1400 to 2300 mg m(-2) inside the iron-enriched patch, while remaining roughly constant in the surrounding waters. Most of the increase inside the patch was associated with the fraction of large (>10 mum) phytoplankton cells, consistent with the shift in the community structure towards larger diatoms. Deck incubations at 60% of the ambient irradiance revealed that the diurnal chlorophyll a (Chl a)-specific production rates of water-extractable polysaccharides were significantly higher for "in-patch" than for "out-patch" samples (0.5 vs. 0.3 mug C [mug Chl a](-1) h(-1), respectively). Together with the higher photochemical efficiency of photosystent II (F-v/F-m), this indicates enhanced photosynthetic performance in response to iron fertilization. In addition, the nocturnal polysaccharide consumption rates were also enhanced by iron release, causing a striking increase in the diel dynamics of polysaccharide concentration. An iron-stimulated increase in diel dynamics was also observed in the fluorescence and size of pico- and nanophytoplankton cells (measured by flow cytometry) and is indicative of enhanced phytoplankton growth. Diurnal polysaccharide production by phytoplankton inside the ...